Regional Morpho-Kinematic Inventory of Slope Movements in Northern Norway - Line Rouyet; Line Rouyet; Line Rouyet; Karianne Staalesen Lilleøren; Martina Böhme; Louise Mary Vick; Reynald Delaloye; Bernd Etzelmüller; Tom Rune Lauknes; Tom Rune Lauknes; Yngvar Larsen; Lars Harald Blikra (Frontiers in Earth Science, 2021)
Mountain slopes in periglacial environments are affected by frost- and gravity-driven processes that shape the landscape. Both rock glaciers and rockslides have been intensively inventoried worldwide. Although most inventories are traditionally based on morphologic criteria, kinematic approaches based on satellite remote sensing have more recently been used to identify moving landforms at the regional scale. In this study, we developed simplified Interferometric Synthetic Aperture Radar (InSAR) products to inventory ground velocity in a region in Northern Norway covering approximately 7,500 km2. We used a multiple temporal baseline InSAR stacking procedure based on 2015–2019 ascending and descending Sentinel-1 images to take advantage of a large set of interferograms and exploit different detection capabilities. First, moving areas are classified according to six velocity brackets, and morphologically associated to six landform types (rock glaciers, rockslides, glaciers/moraines, talus/scree deposits, solifluction/cryoturbation and composite landforms). The kinematic inventory shows that the velocity ranges and spatial distribution of the different types of slope processes vary greatly within the study area. Second, we exploit InSAR to update pre-existing inventories of rock glaciers and rockslides in the region. Landform delineations and divisions are refined, and newly detected landforms (54 rock glaciers and 20 rockslides) are incorporated into the databases. The updated inventories consist of 414 rock glacier units within 340 single- or multi-unit(s) systems and 117 rockslides. A kinematic attribute assigned to each inventoried landform documents the order of magnitude of the creep rate. Finally, we show that topo-climatic variables influence the spatial distribution of the rock glaciers. Their mean elevation increases toward the continental interior with a dominance of relict landforms close to the land-sea margin and an increased occurrence of active landforms further inland. Both rock glaciers and rockslides are mostly located on west-facing slopes and in areas characterised by strongly foliated rocks, which suggests the influence of geological preconditioning factors. The study demonstrates the value of semi-quantitative InSAR products to characterise kinematic information at large scale and exploit the results for periglacial research. It highlights the complementarity of both kinematic and morphologic approaches for inventorying slope processes.